Online social networking: a source of intelligence for advanced persistent threats - Abdul Molok , Nurul Nuha; Ahmad, Atif; Chang, Shanton (IGI Global, 2012)
The professionalization of computer crime has resulted in a shift in motivation away from bragging rights towards financial gain. As a result, the operational tactics of cyber criminals is beginning to incorporate reconnaissance and intelligence gathering to inform attack planning. This paper discusses why information leakage in general, and Online Social Networking (OSN) in particular, has become a source of intelligence for attackers. Further, the paper profiles a range of security measures available to organizations to combat information leakage through OSN and identifies future directions for research into security culture and behaviour change.